Implementation of Customer Relationship Management (CRM) in SME - Rodhiah, Rodhiah; Jocelyn, Fion (CV. Proaksara Global Transeduka, 2025)
Customer Relationship Management (CRM) is a strategy and technology used by companies to manage and strengthen relationships with customers. Customer Relationship Management (CRM) utilizes customer data and information to understand their needs and preferences. Hence, companies can provide better services, increase customer satisfaction, and achieve long-term business success. The business is engaged in the culinary field and is located in Batam. Currently, the business is facing challenges in implementing Customer Relationship Management. The purpose of this activity is to assist the business in improving its understanding of the implementation of Customer Relationship Management and its ability to compete. The method used was CRM-related training on how the business interacts with its customers. The training was conducted online. Through this activity, it is hoped that the problems faced by the business can be overcome.